2021
DOI: 10.29020/nybg.ejpam.v14i3.3985
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Restrained Domination in Graphs

Abstract: Let G be a connected graph. Brigham et al. [3] defined a resolving dominating setas a set S of vertices of a connected graph G that is both resolving and dominating. A set S ⊆ V (G) is a resolving restrained dominating set of G if S is a resolving dominating set of G and S = V (G) or hV (G) \ Si has no isolated vertex. In this paper, we characterize the resolving restrained dominating sets in the join, corona and lexicographic product of graphs and determine the resolving restrained domination number of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…It's noteworthy that the set 𝑆 = 𝑉(𝐺) constitutes a restrained dominating set, and determining is 𝛾 𝑟 (𝐺), an NP-complete decision problem [19]. Several studies on restrained domination in graphs can be found in papers [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It's noteworthy that the set 𝑆 = 𝑉(𝐺) constitutes a restrained dominating set, and determining is 𝛾 𝑟 (𝐺), an NP-complete decision problem [19]. Several studies on restrained domination in graphs can be found in papers [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The dominating set 𝑆 ⊆ 𝑉(𝐺) ∖ 𝐷 is called an inverse dominating set of 𝐺 with respect to a minimum dominating set 𝐷. The concept of inverse domination in graphs was first introduced by Kulli [17], with further information in [18][19][20][21][22][23][24][25][26]. Another type is the disjoint dominating set, defined by Hedetniemi et al [27].…”
Section: Introductionmentioning
confidence: 99%
“…Resolving sets was studied by Slater in [12]. Variations of resolving sets and resolving dominating sets were studied in [2,6,7]. The strong resolving sets and strong metric dimension were introduced and characterized by Oellermann and Peters-Fransen [9].…”
Section: Introductionmentioning
confidence: 99%